Analyzing the storage stability of diesel emulsified fuels: a comparative standpoint. Issue 2 (15th June 2022) - Vasistha, Vishal; Bharj, Rabinder Singh
ABSTRACT: The storage stability of a diesel emulsified fuel plays a crucial role in its commercial application and carries forward its environment-friendly advantage of lowering nitrogen oxides and particulate matter emissions. This article compares storage stability aspects of hydrous ethanol-diesel-Al2 O3 nano (HEDA) and hydrous ethanol-diesel-Al2 O3 nano-Pemulen TR-2 (HEDAP) emulsified fuels via various stability tests (visual inspection, heat storage test, centrifuge test, pH test, density, and viscosity measurements) under freeze-thaw storage condition. The production cost analysis was made to find their commercial suitability. Stability test results found higher storage stability of HEDA fuel, compared to that of HEDAP fuel. A heterogeneous mixing of Pemulen TR-2 and its weaker hydrogen bonding with other compounds could be major factors to lower the stability of HEDAP fuel. The stability of both fuels decreased with an increase in the water proportion. HEDA fuel production cost estimation was found to be lower than HEDAP fuel and slightly higher compared to diesel, which was a good sign of its commercial applicability. The powder X-ray diffraction analysis reported 41.28 nm average crystallites size of Al2 O3 nanoparticles. HEDA emulsified fuel showed better storage stability along with a lower production cost in comparison with the HEDAP fuel. Graphical Abstract: uf0001